Risks of Pneumonia in Patients with Asthma Taking Inhaled Corticosteroids - O'Byrne, Paul M.; Pedersen, Soren; Carlsson, Lars-Göran; Radner, Finn; Thorén, Anders; Peterson, Stefan; Ernst, Pierre; Suissa, Samy (American journal of respiratory and critical care medicine, 2011)
Inhaled corticosteroids (ICS) are the mainstay of asthma treatment. Studies in chronic obstructive pulmonary disease reported increased rates of pneumonia with ICS. Concerns exist about an increased pneumonia risk in patients with asthma taking ICS. To evaluate the risks of pneumonia in patients with asthma taking ICS. A retrospective analysis evaluated studies of the ICS budesonide in asthma. The primary data set were all double-blind, placebo-controlled trials lasting at least 3 months, involving budesonide (26 trials, n = 9,067 for budesonide; n = 5,926 for the comparator) sponsored by AstraZeneca. A secondary data set evaluated all double-blind trials lasting at least 3 months but without placebo control (60 trials, n = 33,496 for budesonide, n = 2,773 for fluticasone propionate). Cox proportional hazards regression modeling was used to estimate the relative effect of ICS on pneumonia adverse events (AEs) or serious adverse events (SAEs). In the primary data set, the occurrence of pneumonia AEs was 0.5% (rate 10.0 events/1,000 patient-years [TPY]) for budesonide and 1.2% (19.3 per TPY) for placebo (hazard ratio, 0.52; 95% confidence interval, 0.36-0.76; P < 0.001); the occurrence of pneumonia SAEs was 0.15% (2.9 per TPY) for budesonide and 0.13% (2.1 per TPY) for placebo (hazard ratio, 1.29; 95% confidence interval, 0.53-3.12; P = 0.58). In the secondary data set, the percentage of patients reporting pneumonia AEs was 0.70% (12.7 per TPY), whereas the percentage of patients reporting pneumonia SAEs was 0.17% (3.1 per TPY). There was no increased risk with higher budesonide doses or any difference between budesonide and fluticasone. There is no increased risk of pneumonia in patients with asthma, identified as an AE or SAE, in clinical trials using budesonide.